2021
DOI: 10.1136/bmjopen-2020-043038
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectoral communication by bringing together patient with cancer, general practitioner and oncologist in a video-based consultation: a qualitative study of oncologists’ and nurse specialists’ perspectives

Abstract: Shared care models in the field of cancer aim to improve care coordination, role clarification and patient satisfaction. Cross-sectoral communication is pivotal. Involvement of patients may add to intended mechanisms.A randomised controlled trial ‘The Partnership Study’ tested the effect of bringing together patient, general practitioner (GP) and oncologist for a consultation conducted by video.PurposeAs part of the process evaluation, this study aimed to explore experiences, attitudes and perspectives of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 41 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Moreover, few studies differentiated between aspects of continuity. Johnsen et al 43 looked specifically at relational and episodic continuity, while Trabjerg et al , 44 Hansen et al , 38 and Tönnies et al 41 reported improved managerial and informational continuity with integrated primary–specialist consultations without referring to it as such, for example, describing ‘more coherent patient trajectory [ies] ’ and ‘roles and tasks [becoming] more apparent to both patients and professionals and [sharing] knowledge between health sectors’. 44 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, few studies differentiated between aspects of continuity. Johnsen et al 43 looked specifically at relational and episodic continuity, while Trabjerg et al , 44 Hansen et al , 38 and Tönnies et al 41 reported improved managerial and informational continuity with integrated primary–specialist consultations without referring to it as such, for example, describing ‘more coherent patient trajectory [ies] ’ and ‘roles and tasks [becoming] more apparent to both patients and professionals and [sharing] knowledge between health sectors’. 44 …”
Section: Resultsmentioning
confidence: 99%
“…Integrated care consultations, for example, whereby the patient and GP were situated together in the GP practice and conducted a joint remote consultation with an oncologist, were shown to improve understanding of the roles of different specialists (such as cancer and mental health) in the patient’s journey, resulting in a more coherent care pathway and improved managerial continuity. 38 , 41 , 44 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations